Muzzle 2 : City of wolves [videorecording (DVD)] - King, Jacob Michael; Eckhart, Aaron; Van Graan, Tanya; Thaning, Karl; Ross, Grant; Uzo; Malawi (RLJE Films, 2026)
Haunted ex-K-9 officer Jake's peaceful life is shattered when a gang brutally attacks his family. With new K-9 partner Argos, he uncovers a drug ring, confronts corrupt officials, and fights inner demons while pursuing the criminals.